Enhancing Economic Decision-Making: The Role of Financial Literacy, Attitudes, and Management Behavior Among Students with Locus of Control as a Mediator - Wukak, Gerasimus I.A.K (Yayasan Riset dan Pengembangan Intelektual, 2024)
The aim of this research is to prove the influence of financial literacy and financial attitudes on financial management behavior with locus of control as an interventing variable in students at the Wiayata Taman Siswa Faculty of Economics. The population or sample in this research was 100 students from the Faculty of Economics at Wiayata Taman Siswa University. The data collection method uses questionnaires. Analysis of data quality tests using validity tests and reliability tests. The data analysis technique uses multiple regression analysis which includes the classical assumption test, normality test, multicollinearity test, and heteroscedasticity test. Hypothesis testing using the T test, F test, and R2 test using the Sobel test using the SPSS version 23 program. The results of the research show that literacy variables, financial attitudes, financial locus of control influence financial management behavior variables and the intervening variable locus of control is considered to be effective. mediates the relationship between financial literacy and financial management behavior and the intervening variable locus of control is considered to mediate the relationship between financial attitudes and financial management behavior.